The Effect of Product Aggregation in Determining Sales Variances. - Malcom, Robert E. (The Accounting Review, 1978)
Abstract ABSTRACT: While current management accounting texts are in general agreement regarding the usefulness and general calculation methods for sales variance determination, they do not consider the effects of alternative product reporting classifications on the analysis. For sales variances, different product aggregations basically change the character of the analysis. For example, whereas a detailed analysis might show each product having a positive price change, an aggregated analysis could show a negative price change. The objective of this article is to indicate such possible effects and to make recommendations to avoid difficulties. Alternative analyses from a single data set are developed to illustrate the potential problems. Conclusions are that aggregated products should have margins as homogeneous as possible and that great care must be exercised in reports to indicate the level to which any mix variance applies.